Complementary Feeding of Sorghum-Based and Corn-Based Fortified Blended Foods Results in Similar Iron, Vitamin A, and Anthropometric Outcomes in the MFFAPP Tanzania Efficacy Study. Issue 6 (10th April 2019) - Delimont, Nicole M; Vahl, Christopher I; Kayanda, Rosemary; Msuya, Wences; Mulford, Michael; Alberghine, Paul; Praygod, George; Mngara, Julius; Alavi, Sajid; Lindshield, Brian L
ABSTRACT: Background: Fortified blended foods (FBFs) are micronutrient-fortified food aid products containing cereals and pulses. It has been suggested to reformulate FBFs to include whey protein concentrate, use alternative commodities (e.g., sorghum and cowpea), and utilize processing methods such as extrusion to produce them. The Micronutrient Fortified Food Aid Pilot Project (MFFAPP) efficacy study was designed to test the efficacy of complementary feeding of newly formulated FBFs. Objectives: The aim of this study was to test the effectiveness of 5 newly formulated FBFs in combating iron deficiency anemia and vitamin A deficiency compared with traditionally prepared corn-soy blend plus (CSB+) and no intervention. A secondary aim was to determine the impact on underweight, stunting, wasting, and middle-upper arm circumference. Methods: A 20-wk, partially randomized cluster study was completed. Two age groups (aged 6–23 and 24–53 mo) with hemoglobin status <10.3 g/dL, and weight-for-height z scores >−3 were enrolled and assigned to diet groups. Biochemical and anthropometric measurements were collected at 0, 10, and 20 wk. Results: Both hemoglobin concentrations and anemia ORs were significantly improved in all intervention groups except for CSB+ and the no-intervention groups at week 20. Only extruded corn-soy blend 14 and the no-intervention age groups failed to significantly decrease vitamin A deficiency risk ( P  < 0.04). There were no consistent significant differences among groups in anthropometric outcomes. Conclusions: FBFs reformulated with sorghum, cowpea, corn, and soy significantly improved anemia and vitamin A deficiency ORs compared with week 0 and with no intervention. Although newly formulated FBFs did not significantly improve vitamin A deficiency or anemia compared with CSB+, CSB+ was the only FBF not to significantly improve these outcomes over the study duration. Our findings suggest that newly formulated sorghum- and cowpea-based FBFs are equally efficacious in improving these micronutrient outcomes. However, further FBF refinement is warranted. This trial was registered at clinicaltrials.gov as NCT02847962.